2011
DOI: 10.1143/jjap.50.04dg19
|View full text |Cite
|
Sign up to set email alerts
|

GaN-Based Metal–Semiconductor–Metal Ultraviolet Photodetectors with the ZrO2Insulating Layer

Abstract: GaN metal–semiconductor–metal (MSM) ultraviolet (UV) photodetectors (PDs) with ZrO2 insulating layers were successfully fabricated and characterized. It was found that we can achieve a small dark current and large photocurrent to dark current contrast ratio from the proposed devices with the use of ZrO2 insulating layers. With a 20 V applied bias, it was found that the leakage current of the fabricated MSM PDs with ZrO2 insulating layers was 1.73 ×10-10 A. This small leakage current should be attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For example, Lee et al used a 130 nm thick GaO x interlayer for achieving a photo‐to‐dark current ratio of ≈10 6 where a peak responsivity of 9 A W −1 was demonstrated. On the other hand, Chen et al reported a photo‐to‐dark current ratio of ≈10 3 using only a 30 nm thick insulating layer of ZrO 2 where a peak responsivity of only 0.02 A W −1 was reported. Yet, in another report, a photo‐to‐dark current ratio of ≈10 4 and a peak responsivity of 1.42 A W −1 were demonstrated by inserting a very thin (only 1.5 nm) layer of HfO 2 .…”
Section: A Summary Of Schottky Junction Parameters Estimated Using Thmentioning
confidence: 79%
See 1 more Smart Citation
“…For example, Lee et al used a 130 nm thick GaO x interlayer for achieving a photo‐to‐dark current ratio of ≈10 6 where a peak responsivity of 9 A W −1 was demonstrated. On the other hand, Chen et al reported a photo‐to‐dark current ratio of ≈10 3 using only a 30 nm thick insulating layer of ZrO 2 where a peak responsivity of only 0.02 A W −1 was reported. Yet, in another report, a photo‐to‐dark current ratio of ≈10 4 and a peak responsivity of 1.42 A W −1 were demonstrated by inserting a very thin (only 1.5 nm) layer of HfO 2 .…”
Section: A Summary Of Schottky Junction Parameters Estimated Using Thmentioning
confidence: 79%
“…Insertion of an insulating layer between metal and semiconductor is an effective technique for suppressing the leakage current and also for improving an overall performance of PDs. A significant reduction in the leakage current is already reported by several researchers by incorporating various insulating layers, such as SiO 2 , ZrO 2 , GaO x , and Al 2 O 3 . Although a considerable amount of work is already carried out on GaN‐based metal–insulator–semiconductor (MIS) PDs, a consensus among researchers is yet to arrive on the choice of material and thickness of the insulating layer.…”
Section: A Summary Of Schottky Junction Parameters Estimated Using Thmentioning
confidence: 99%
“…Various insulating materials such as SiO 2 , ZrO 2 , and Al 2 O 3 are reported. [14][15][16] However, low dielectric constant (k) value restricts the maximum permissible electric field to the device. Therefore, high-k insulating material is helpful in reducing the field strength within the dielectric and thus allowing better performance of the devices.…”
Section: Introductionmentioning
confidence: 99%
“…6) In this respect, ZrO 2 might be considered as a suitable gate insulator for GaN-based MOSHFETs due to its high dielectric constant (20-25) and good thermal stability. 7) Recent increased interest in the application of ZrO 2 dielectric on GaN is related not only to transistors, but also to photodetectors 8) and light-emitting diodes. 9) Published results on GaN-based MOSHFETs (i.e., on AlGaN/GaN as well as InAlN/GaN) with ZrO 2 gate insulator can be summarized as follows: static characterization confirms general features of MOS devices, such as suppressed gate leakage current and increased drain current in comparison with HFETs, 4,[9][10][11][12] increased or only slightly decreased transconductance is observed due to a high permittivity of the gate insulator.…”
Section: Introductionmentioning
confidence: 99%